2017
DOI: 10.1038/ncomms14531
|View full text |Cite
|
Sign up to set email alerts
|

Place cells are more strongly tied to landmarks in deep than in superficial CA1

Abstract: Environmental cues affect place cells responses, but whether this information is integrated versus segregated in distinct hippocampal cell populations is unclear. Here, we show that, in mice running on a treadmill enriched with visual-tactile landmarks, place cells are more strongly controlled by landmark-associated sensory inputs in deeper regions of CA1 pyramidal layer (CA1d). Many cells in CA1d display several firing fields correlated with landmarks, mapping positions slightly before or within the landmarks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
123
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 46 publications
8
123
3
Order By: Relevance
“…Thus, one may speculate that, through separate output channels, the superficial CA1 sublayer conveys a more stable spatial map of the environment while the deep sublayer represents dynamic features, such as reward location, to support learning, providing a potential solution for the stability–plasticity dilemma of memory networks. Consistent with this reasoning, a recent study using silicone probe recordings showed 90 that firing fields in a subset of deep CA1PCs are more tightly linked to the location of individual sensory stimuli (i.e., landmarks on the navigation belt), while the superficial layer contained CA1PCs that were more likely to represent a global spatial context. Together, these studies on radial CA1PC subdivisions provide strong support for a conceptual framework in which hippocampal output neurons are parsed into parallel nonuniform subcircuits, supporting distinct cognitive functions.…”
Section: Functional Heterogeneity Of Ca1pc In the Context Of Behaviormentioning
confidence: 65%
See 1 more Smart Citation
“…Thus, one may speculate that, through separate output channels, the superficial CA1 sublayer conveys a more stable spatial map of the environment while the deep sublayer represents dynamic features, such as reward location, to support learning, providing a potential solution for the stability–plasticity dilemma of memory networks. Consistent with this reasoning, a recent study using silicone probe recordings showed 90 that firing fields in a subset of deep CA1PCs are more tightly linked to the location of individual sensory stimuli (i.e., landmarks on the navigation belt), while the superficial layer contained CA1PCs that were more likely to represent a global spatial context. Together, these studies on radial CA1PC subdivisions provide strong support for a conceptual framework in which hippocampal output neurons are parsed into parallel nonuniform subcircuits, supporting distinct cognitive functions.…”
Section: Functional Heterogeneity Of Ca1pc In the Context Of Behaviormentioning
confidence: 65%
“…Recent studies demonstrated that stable and labile place coding elements, segregated along the CA1 radial axis, show distinct in vivo physiological properties and differentially predict learning of rewarded spatial locations and show that these elements are differently interconnected through GABAergic circuits 43,8183,85,90,94 . These results, together with other studies on the dorsoventral and proximodistal axes of hippocampus (reviewed in refs 46,47 ), raise questions about the nature of relationships between PC subcircuits and hippocampal-dependent behaviors.…”
Section: Open Questions About Heterogeneity Of Principal Neurons In Tmentioning
confidence: 99%
“…In single hippocampal neurons, nodal coding manifests in a wide variety of firing patterns that occur in a general manner across different single experiences: for example, firing in place cells that encodes regular features of a subject's spatial experience (e.g., spatial firing fields in similar or analogous locations across different environments) rather than single locations (e.g., Skaggs & McNaughton, 1998). The existence and ubiquity of this type of coding is reported in a collection of place cell studies reporting two contrasting firing patterns (typically observed in different cells—often CA1 neurons—in the same recording): firing that is specific to a spatial location or spatial behavior (referred to as “context”‐specific place firing; e.g., directional place firing, trajectory or “splitter” place firing, journey place firing) as opposed to firing that occurs across these locations and behaviors (e.g., “pure” place cells, “bidirectional” place cells, “path equivalent” firing; findings reviewed in Eichenbaum et al (); Eichenbaum and Cohen (); example studies include McNaughton et al (); Gothard, Skaggs, Moore, and McNaughton (); Skaggs and McNaughton (); Wood, Dudchenko, and Eichenbaum (); Frank, Brown, and Wilson (); Wood, Dudchenko, Robitsek, and Eichenbaum (); Ferbinteanu and Shapiro (); Battaglia, Sutherland, and McNaughton (); Smith and Mizumori (); Royer, Sirota, Patel, and Buzsaki (); Singer, Karlsson, Nathe, Carr, and Frank (); Grieves, Wood, and Dudchenko (); Geiller et al ()). In addition to this work in the rodent model, it is also important to note that nodal coding encompasses the invariant firing correlates of hippocampal neurons reported in humans (Quiroga, ; Quiroga et al, ).…”
Section: Three Brain States In the Hippocampusmentioning
confidence: 99%
“…In contrast, CA1 PNs towards subiculum (distal CA1) display higher tuning for objects and odors (Burke et al, 2011; Ito and Schuman, 2012; Nakamura et al, 2013; Igarashi et al, 2014). Across the radial axis, multiple studies have demonstrated that deep PNs encode more spatial information than superficial neurons (Mizuseki et al, 2011; Oliva et al, 2016), yet superficial PNs may provide a more stable environmental map and respond slowly to manipulation of spatial landmarks (Danielson et al, 2016; Geiller et al, 2017). This dichotomy is further supported by another study that reported a morphological subtype of CA1 PN, that tends to lie more superficially, that is highly responsive to odors (Li et al, 2017).…”
Section: Functional Heterogeneity Of Ca1 Pyramidal Neuronsmentioning
confidence: 99%